Perbandingan Model Asuhan Keperawatan Profesional Tim dengan Primary Nursing dalam Peningkatan Kualitas Asuhan Keperawatan di Rumah Sakit Kota Medan - Hendry Kiswanto Mendrofa; Muhammad Taufik Daniel Hasibuan (Jurnal Riset Hesti Medan, 2021)
The development of science and technology that continues to progress, especially in the health sector requires changes in terms of service so that in providing more professional services in hospitals, nursing care must be of high quality. Nursing Law Number 38 of 2014 Article 3B states that nursing arrangements aim to improve the quality of nursing services, therefore the provision of quality nursing services is important in today's health services. The model of professional nursing care is divided into several models, namely primary, team and case nursing. Based on the results of a survey of research journals, the researchers concluded that there was no research that compared the professional nursing care team model with primary nursing in improving the quality of nursing care. The purpose of this study was to identify the use of the professional nursing care team model with the primary nursing model in improving the quality of nursing care. This type of research is a quantitative research type with a comparative design. The population in this study were all patients at the Inpatient Hospital where the study was conducted. The sampling technique used was purposive sampling technique. Data collection on the quality of nursing care used a quality scale patient assessment instrument – the acute care version (PAQS-ACV). This instrument was developed to assess the quality of nursing care. Data analysis in this study used an independent t-test. normality test using the Kolmorogov-Smirnov test with a significance value (p > 0.05). The results showed that there was a significant difference between the quality of nursing care in the team group and the quality of nursing care in the primary nursing group where the value of sig (2-tailed) was 0.008 where > 0.05, the results also showed that based on the results of the frequency distribution test the quality of nursing care was using the team model and the primary nursing model has a high majority value of nursing care quality, but there is a difference in the average value (mean) where the quality of nursing care in the nursing care model group in the team method group is 144.86 and the quality of nursing care in the primary nursing model group is 155.83. These results indicate that the quality of nursing care with the primary nursing model has a higher quality of care value than the group nursing care model with the team method. Based on the results of this study, it is recommended that hospitals can apply a professional nursing practice model, especially the primary nursing model to further improve the quality of nursing care provided.